Implementation Culturally Responsive Teaching Approach to Improve Student Learning Outcomes - Wati, Siskawati Siska; Handayani, Baiq Sri; Lestari, Tri Ayu; Hadratullaili, Hadratullaili (Universitas Islam Negeri Mataram, 2023)
Learning using an approach that suits student characteristics will influence learning outcomes. Soan approach is needed that suits the students' abilities. One suitable approach is CRT (Culturally Responsive Teaching) by applying the PjBL (Project Based Learning) model which is relevant to students' lives, from characteristics to students' culture, which will greatly influence student learning outcomes, so an approach is needed that suits students' learning needs. relevant and contextual. The CRT approach is a learning approach that recognizes the importance of students' cultural references in all aspects of learning.This research aims to improve the learning outcomes of class XII IPA 1 students by applying the CRT approach. This research was carried out by conducting classroom action research which was divided into two cycles. Data was obtained from observation, pretest and posttest cycles 1 and 2. Data analysis techniques in this research used qualitative and quantitative analysis. The results of research using the application of PjBL integrated with the CRT approach in cycle 1 reached 75.00 and in cycle 2 it increased to 85.00. This shows that the application of the CRT approach in the learning process can improve the learning outcomes of class XII IPA 1 students on Biotechnology lesson